Sonography of the first metatarsophalangeal joint and sonographically guided intraarticular injection of corticosteroid in acute gout attack. Issue 3 (9th July 2014) - Kang, Myung Ho; Moon, Ki Won; Jeon, Yong Hwan; Cho, Seong Whi
ABSTRACT Objective The aims of this study were to identify the characteristic ultrasound (US) findings of the first metatarsophalangeal joint (MTPJ1) in acute gout attack and to evaluate the efficacy and safety of US‐guided intraarticular corticosteroid injection of the MTPJ1. Methods We enrolled 21 patients with acute gout attack involving the MTPJ1 unilaterally. US evaluation of each affected MTPJ1 was compared with radiographic features. US‐guided intraarticular corticosteroid (0.5 ml [20 mg] of triamcinolone mixed with 0.5 ml of 2% lidocaine) was injected into the affected MTPJ1s. Pain, general disability, and walking disability were assessed at baseline, 24 hours, 48 hours, and 7 days after injection with visual analog scales. Results The characteristic US findings of MTPJ1 were erosion, joint effusion, synovial hypertrophy, tophus‐like lesion, double contour, hyperechoic spots, and increased power Doppler signal in acute gout attack. US was more sensitive than conventional radiograph in detecting erosion and tophus‐like lesion. The reductions of mean visual analog scale scores in pain, general disability, and walking disability were 48 mm (SD, 27), 35 mm (SD, 26) and 39 mm (SD, 26), respectively, 48 hours after US‐guided intraarticular corticosteroid injection. There were no adverse events. Conclusions US is a sensitive tool to evaluate joint abnormality of the MTPJ1 in acute gout attack and US‐guided intraarticular corticosteroid injection to this joint is effective and safe. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:179–186, 2015;